(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Patients with HF experience high levels of anxiety and depression and their quality of life decreases significantly. Mental health illnesses are associated with frequent hospitalizations and increased risk. Off all-cause was mortality. This study was conducted to know the mental health of HF patients. Cross sectional study was conducted at an outpatient’s HF clinic in a tertiary teaching hospital. The study participants completed a DASS-21 questionnaire to screen for the presence and severity of depression, anxiety and stress symptoms. MMAS-8 was used to screen the patient adherence to medication. Out of 100 patients, 53.6% of patients are normal without any psychiatric symptoms, and 46.4% of patients are suffering from psychiatric symptoms. Among them, 17.3% of patients have mild symptoms, 24% have moderate symptoms, and only 5% have severe symptoms related to depression, anxiety & stress. Of 100 patients, 54% have low adherence, 28% have medium adherence, and 18% have high adherence. HF is one of the most clinical diseases associated with a significant reduction in the QOL. Psychiatric symptoms are common in HF patients and they have low medication adherence. Hence, multimodal treatment approach such as collaborative care models or stepped care from mental health professionals are needed to improve psychiatric and cardiac health.